Dermatoskopie bei malignen und benignen Hauttumoren - Blum, Andreas; Hänßle, Holger (Der Hautarzt, 2017)
Dermoscopy has a high diagnostic accuracy in pigmented and nonpigmented malignant and benign skin tumors. These microscopic in vivo examinations with polarized and nonpolarized light are effective in the early detection of malignant skin tumors and reduce the number of unnecessary excisions of benign skin tumors. The selection of the skin lesions is crucial for the diagnostic accuracy of the dermoscopic examination. Not only large pigmented skin lesions, but also small hypo-, de-, or nonpigmented skin lesions, should be examined dermatoscopically as well as skin lesions that have changed in shape and/or color. In clinical routine, research and teaching, the dermoscopic diagnosis should be performed by describing the visible structures, their distribution and colors by means of descriptive and/or metaphoric terminology. Optionally, a diagnostic algorithm can also be used. Especially in benign lesions, the dermatoscopic diagnosis should be uniform for the complete area. Comparison with other nearby skin tumors of the same patient (comparative approach) is helpful in the evaluation of numerous melanocytic skin tumors. If it is unclear whether the lesion is malignant, a biopsy or complete excision should be performed with subsequent histopathological examination.